Insight into the performance and mechanism of magnetic Ni0.5Cu0.5Fe2O4 in activating peroxydisulfate for ciprofloxacin degradation - Wang, Bo (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Magnetic nickel-copper ferrite (NixCuyFe2O4) nano-catalyst was synthesized by co-precipitation method, and it exhibited excellent ability for activating peroxydisulfate (PDS) in the degradation of ciprofloxacin (CIP). As-prepared Ni0.5Cu0.5Fe2O4 properties were characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope equipped with an energy-dispersive X-ray (SEM-EDX), transmissions electron microscopy (TEM), N2 adsorption-desorption isotherm plot of Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH), vibrating sample magnetometer (VSM). The maximum degradation efficiency is 80.2% by using 0.500 g/L of Ni0.5Cu0.5Fe2O4 for activating 5.00 mmol/L of PDS to degrade CIP (20.0 mg/L) at 25 ± 2 °C for 50 min (pH = 6.00). The presence of interfering ions Cl-, NO3-, and HCO3- inhibited the reaction by producing reactive species with low oxidation potential, inducing the degradation efficiency down to 60.0%, 58.1% and 21.5% respectively. Ni0.5Cu0.5Fe2O4 displayed great magnetic separation characteristic for the satisfactory magnetization; saturation value is ∼8.6 emu/g. The degradation efficiency of recycled samples has no significant difference after using three times, which is about 60%, indicating that Ni0.5Cu0.5Fe2O4 is a reusability catalyst in activating PDS for CIP degradation. This work might provide an efficient and promising approach to construct recyclable magnetic materials that can be used for wastewater treatment